Functional assessment of renal damage in children with primary vesicoureteral reflux - Zhu, Yaju; Li, Yufeng; Jin, Jing; Ni, Jiajia (Frontiers in Pediatrics, 2025)
ObjectivesTo evaluate the renal function damage in children with primary vesicoureteral reflux (VUR).MethodsA total of 226 children with VUR (65 cases with left, 39 with right, and 122 cases with bilateral VUR) were screened. Eighty-five urinary tract infection (UTI) cases, without urinary malformations, during the same period were collected as controls. Age at diagnosis, body weight, renal ultrasound, VUR grade, serum creatinine level, dimercaptosuccinic acid (DMSA) level, and effective renal plasma flow (ERPF) values were retrospectively analyzed.ResultsThere were no significant differences in age at diagnosis between study groups. Total ERPF was significantly lower in the bilateral VUR group than in the control group. The ERPF in unilateral VUR was significantly lower than that in the contralateral or ipsilateral side in the control group (P < 0.001). The mean split renal function, as assessed by DMSA of VUR, was 28.00% and 29.12% on the left and right sides, respectively, both of which were lower than the control group's 40.27%. Renal damage was also correlated with a VUR grade (P = 0.008), a transverse diameter (P = 0.002), and pyelectasis (P = 0.037).ConclusionSplit renal function was impaired in the reflux kidney. The total ERPF in the bilateral VUR group was lower than that in the unilateral VUR group. Renal damage was correlated with a VUR grade, a transverse diameter, and pyelectasis.